STRATEGI PENGEMBANGAN USAHATANI KOPI LIBERIKA (COFFEE LIBERICA) DI DESA KADARUPAT KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Yolanda Fisca Jonna; Hendro Ekwarso; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to know, analyze and analyze the strategy of coffee farming development in order to increase production so as to increase the income of coffee farmers in Meranti Island Riau. The data used are secondary and primary data. Secondary data were obtained from the central statistical agency (BPS) of riau islands. Primary data obtained from questionnaires and interviews based on direct observation method at coffee farmers located in the village of kadarupat and using the key person in determining the sample, the sample in this study as many as 15 coffee farmers. Data analysis used in this research is descriptive by using SWOT Analysis Based on the results of SWOT analysis by combining internal factor matrix and external factors then drawing the conclusion from the diagram of strategy formation supported by SWOT matrix then Position of kadaburapat village coffee farming in SWOT position matrix is in quadrant IV (-0,27; -0,98) so that alternative development strategy recommended is defensive strategy that is by increasing farmer's capital through government support by holding capital institution and promoting extension activity needed by coffee farmer, utilizing appropriate technology for extension worker in performing its duty, government in the development of facilities and infrastructure needed by farmers in the framework of the development of farming.Keywords : coffee farming, SWOT analysis, government role